ПРОБЛЕМИ ПОКОЛІННЯ КРІЗЬ ПРИЗМУ ЛІРИЧНОГО БАЧЕННЯ СЕРГІЯ ЖАДАНА (НА МАТЕРІАЛІ ЗБІРКИ “БАЛАДИ ПРО ВІЙНУ І ВІДБУДОВУ”) - Maltsev, Valentyn; Tsivinska, Yuliia (Буковинський державний медичний університет, Сучавський університет імені Штефана чел Маре, 2021)
Valentyn Maltsev, Yuliia Tsivinska. Problems of the generation through the prism of Serhii Zhadan's lyrical vision (based on the collection “Ballads about war and reconstruction”). The aim of the study is to identify the problems of the generation of the 1990s, raised in the poetry collection of S. Zhadan “Ballads of war and reconstruction” and to clarify the specifics of the author's vision of their causes and impact on society. Research methods: cultural-historical, biographical, comparative. Scientific novelty. For the first time, the article analyzes the author's artistic vision of the crisis of the generation of the 90s, acute social problems, the causes of which are caused by the socio-political circumstances of the last century, and also highlights the key thematic features of the collection. Conclusions. The collection “Ballads of war and reconstruction” is the author's revelation about his attitude to the past. S. Zhadan does not hide anything and not afraid to be incomprehensible. The poet does not disguise the truth and does not try to smooth it out. The collection contains works that raise important problems of the last century, including war, its consequences and influence on the formation of consciousness of subsequent generations, the destruction of cultural figures by the Soviet regime, population migration and criticism of the political system. The author draws attention to details that often contradict the subject and the dissonance “high / low” becomes noticeable. But this technique only exacerbates the problem, causes even more attention and reflection. In general S. Zhadan's collection testifies to the development of the author's style at different levels as well as continues the main motives of his literary work and shows the peculiarities of artistic vision. Prospects for further research of S. Zhadan's poetic work are seen in the observation of the development and in the detailed analysis of the problems and topics of the author's collections of poems as well as in the study of emphony, stylistic and artistic means in his texts, features of versification etc.
Keywords: Сергій Жадан; поезія; збірка; мотив; образ; символ; міграція; відновлення; криза; покоління